2016
DOI: 10.2967/jnumed.115.157859
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT for Staging and Restaging of Breast Cancer

Abstract: Many studies have pointed out the role of 18 F-FDG PET/CT (or 18 F-FDG PET) in patients with clinical stage III or II breast cancer. 18 F-FDG PET/CT might advantageously replace other staging procedures, such as bone scanning and possibly contrast-enhanced CT of the thorax or abdomen-pelvis. We discuss the findings, locoregional or distant, that can be expected in different categories of breast cancer and their impact on prognosis and management. We also discuss the role of 18 F-FDG PET/CT in restaging and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
122
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 59 publications
8
122
0
2
Order By: Relevance
“…25,26 Although 18 F-FDG PET/CT can inform the decision to omit SLNB for patients who show FDG-avid ALN because of its high specificity, it cannot be used as a substitute for SLNB even if 18 F-FDG PET/CT is negative in the axilla because its reliability is very low. 7 However, 18 F-FDG uptake by primary tumor reflects not only metabolic information but also tumor aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Although 18 F-FDG PET/CT can inform the decision to omit SLNB for patients who show FDG-avid ALN because of its high specificity, it cannot be used as a substitute for SLNB even if 18 F-FDG PET/CT is negative in the axilla because its reliability is very low. 7 However, 18 F-FDG uptake by primary tumor reflects not only metabolic information but also tumor aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies included the more advanced stages, stage III and IV, and a few studies included post-operative patients. Many issues of importance are relevant for breast cancer, notably the emerging role of PET/MRI and its comparison with PET/CT[47], the use of PET in the monitoring of neoadjuvant therapy[48], the use for staging and restaging[49], the standardized uptake values (commonly known as SUVs) and how they relate to lymph node status[50], the prognostic role of FDG-PET[51] and the suitability for treatment planning[52]; all these represent immensely exciting domains of breast cancer research, but would have confused the scope of the present study, namely the rates of DM.…”
Section: Discussionmentioning
confidence: 99%
“…PET/CT has shown a high accuracy to detect extra-axillary lymph nodes and distant metastases [2]. Given the high incidence of BC and known inconvenience of FDG imaging (such as high cost, radiation exposure, potential false positive findings and risk for delaying care), PET should be used in specific sub-groups only, especially in patients with high risk of distant metastases.…”
mentioning
confidence: 99%
“…The larger evaluations have been performed in locally advanced and inflammatory BC [6][7][8] which are usually regarded as equivalent to stage III cancer of the AJCC classification [9]. More recent studies have suggested that PET/CT could also be valuable in stage II patients, especially in stage IIB [2,10,11]. In 254 patients with BC of mixed phenotypes, we detected distant metastases with PET/CT in 2.3% (1/44) of clinical stage IIA, 10.7% (6/56) of stage IIB, 17.5% (11/63) of stage IIIA, 36.5% (27/ 74) of stage IIIB and 47.1% (8/17) of stage IIIC patients [11].…”
mentioning
confidence: 99%